Fishing effort alternatives for the management of demersal fisheries in the western Mediterranean - Martín, Paloma; Maynou, Francesc; Garriga-Panisello, Mariona; Ramírez, John; Recasens, Laura (Scientia Marina, 2019)
Management alternatives based on fishing effort for the demersal fisheries in the western Mediterranean were tested, with the novelty of examining management alternatives at temporal scales smaller than one year. Nine scenarios were considered on the basis of input control: decrease in the number of fishing days, which may correspond to cessation of activity of vessels or lower activity of the fleet; and implementation of seasonal closures of one-, two- and three-month duration in winter, spring, summer and autumn. The approach is based on a multispecies and multigear bioeconomic model. We selected a total of ten species (Merluccius merluccius, Nephrops norvegicus, Mullus barbatus, Mullus surmuletus, Parapenaeus longirostris, Lophius piscatorius, Lophius budegassa, Aristeus antennatus, Phycis blennoides and Lepidorhombus boscii) and seven fleets, defined as a combination of fishing gear (bottom trawl, entangling nets and longline) and fleet segment. A similar decrease in F is achieved with a 20% reduction of fishing effort (days) or with two- to three-month closures. Maximum Sustainable Yield (MSY) for all stocks would be achieved only with such a drastic reduction of fishing effort ( > 80% of fishing days by the end of the five years of simulation) that, in practice, its application can be considered unrealistic, since it would represent a very low activity of all fishing fleets over the year.